ACCOMPANIENT FOR BAKBAK TRADEMARK REGISTRATION AS INTELLECTUAL PROTECTION - Nopiana Nopiana; Tantimin Tantimin (ConCEPt - Conference on Community Engagement Project, 2022)
Companies in the world have had various kinds of signs with their own characteristics. The sign intended to distinguish these products is referred to as a brand. Brands can also be used to provide prevention against unfair business competition. The problem that occurs in current field practice is the low level of awareness of the importance of trademark registration. So the activity of Community Service (PKM) from the author is BakBak which is an MSME that follows the current culinary trends with unique rice bowls that use processed pork, so because there is BakBak's own uniqueness, it is necessary to register its brand in order to have legal certainty and be legally protected.